A delivery system specifically approaching bone resorption surfaces to facilitate therapeutic modulation of microRNAs in osteoclasts. (June 2015) - Liu, Jin; Dang, Lei; Li, Defang; Liang, Chao; He, Xiaojuan; Wu, Heng; Qian, Airong; Yang, Zhijun; Au, Doris W.T.; Chiang, Michael W.L.; Zhang, Bao-Ting; Han, Quanbin; et al.
Abstract: Dysregulated microRNAs in osteoclasts could cause many skeletal diseases. The therapeutic manipulation of these pathogenic microRNAs necessitates novel, efficient delivery systems to facilitate microRNAs modulators targeting osteoclasts with minimal off-target effects. Bone resorption surfaces characterized by highly crystallized hydroxyapatite are dominantly occupied by osteoclasts. Considering that the eight repeating sequences of aspartate (D-Asp8 ) could preferably bind to highly crystallized hydroxyapatite, we developed a targeting system by conjugating D-Asp8 peptide with liposome for delivering microRNA modulators specifically to bone resorption surfaces and subsequently encapsulated antagomir-148a (a microRNA modulator suppressing the osteoclastogenic miR-148a), i.e. (D-Asp8 )-liposome-antagomir-148a. Our results demonstrated that D-Asp8 could facilitate the enrichment of antagomir-148a and the subsequent down-regulation of miR-148a in osteoclasts in vivo, resulting in reduced bone resorption and attenuated deterioration of trabecular architecture in osteoporotic mice. Mechanistically, the osteoclast-targeted delivery depended on the interaction between bone resorption surfaces and D-Asp8 . No detectable liver and kidney toxicity was found in mice after single/multiple dose(s) treatment of (D-Asp8 )-liposome-antagomir-148a. These results indicated that (D-Asp8 )-liposome as a promising osteoclast-targeting delivery system could facilitate clinical translation of microRNA modulators in treating those osteoclast-dysfunction-induced skeletal diseases.